AN ANALYSIS OF PUBLIC DEBT LEVELS IN BOTH DEVELOPED AND DEVELOPING COUNTRIES - Arsić, Sonja S; Obradović, Jelena; Stojanović, Miloš (International Journal of Economic Practice and Policy, 2015)
The main objective of this paper is pointing out the importance of high public debt problem as well as the underlying causes that have led to rise in public debt in selected countries. The following methods were used in this research: historical method, deduction, generalization methods and statistical methods. By observing data on ten-year trend of public debt in selected countries, we have concluded that there is a trend of increase in public debt, as a percentage of the gross domestic product of a country. Each of the analyzed countries (Canada, United Kingdom, Greece, Argentina and Serbia) has specific causes that have led to rise in public debt, but the main cause that is common to all countries is the excessive consumption of state organs and reduction of tax revenues that has arisen as a result of reduced economic activity due to the global economic crisis in recent years. By analyzing the data on the trend of public debt in the observed countries in the period from 2003. to 2014., we have concluded that the problem can be solved by increasing gross domestic product, or reducing government spending.